2011
DOI: 10.1016/j.toxicon.2011.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic action of Bothriopsis bilineata smargadina (forest viper) venom in vitro

Abstract: In this work, we examined the neuromuscular activity of Bothriopsis bilineata smargadina (forest viper) venom in vertebrate isolated nerve-muscle preparations. In chick biventer cervicis preparations the venom caused concentration-dependent (0.1-30 μg/ml) neuromuscular blockade that was not reversed by washing, with 50% blockade occurring in 15-90 min. Muscle contractures to exogenous acetylcholine and KCl were unaffected by venom, but there was a slight increase in creatine kinase release after 120 min (from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 24 publications
0
12
0
5
Order By: Relevance
“…Mouse phrenic nerve‐hemidiaphragm preparations were incubated for 120 min either with B. jararacussu venom (100 μg/mL), B. bilineatus venom (30 μg/mL), BthTX‐I (50 μg/mL) or Bbil‐TX (3 μg/mL) in Tyrode solution (composition in mM: NaCl 137, KCl 2.7, CaCl 2 1.8, MgCl 2 0.49, NaH 2 PO 4 0.42, NaHCO 3 11.9 and glucose 11.1; pH 7.5 at 37°C) and constantly aerated by carbogen (95% O 2 −5% CO 2 ), while control samples were exposed to Tyrode solution ( n = 4 per group). The concentrations of venoms and toxins are the same previously shown to induce neuromuscular blockade (Floriano et al, ; Oshima‐Franco et al, ; Rodrigues‐Simioni et al, ).…”
Section: Methodsmentioning
confidence: 59%
See 1 more Smart Citation
“…Mouse phrenic nerve‐hemidiaphragm preparations were incubated for 120 min either with B. jararacussu venom (100 μg/mL), B. bilineatus venom (30 μg/mL), BthTX‐I (50 μg/mL) or Bbil‐TX (3 μg/mL) in Tyrode solution (composition in mM: NaCl 137, KCl 2.7, CaCl 2 1.8, MgCl 2 0.49, NaH 2 PO 4 0.42, NaHCO 3 11.9 and glucose 11.1; pH 7.5 at 37°C) and constantly aerated by carbogen (95% O 2 −5% CO 2 ), while control samples were exposed to Tyrode solution ( n = 4 per group). The concentrations of venoms and toxins are the same previously shown to induce neuromuscular blockade (Floriano et al, ; Oshima‐Franco et al, ; Rodrigues‐Simioni et al, ).…”
Section: Methodsmentioning
confidence: 59%
“…Adult specimens can achieve 75–100 cm length; its green colour with black spots helps the camouflage for attacking the prey (Figure B). In vitro studies show that the venom of B. bilineatus causes neuromuscular blockade in avian and mammalian isolated nerve‐muscle preparations, and this effect has been attributed to a presynaptic mechanism of action PLA 2 ‐dependent (Rodrigues‐Simioni et al, ) with no apparent myotoxic effect. Recently, a presynaptic‐active Asp49‐PLA 2 (Bbil‐TX) was purified and characterized from this venom (Carregari et al, ), which appears to be responsible for the neurotoxicity shown by crude venom in vitro (Floriano et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that the BrtX-I from Bothrops moojeni did not significantly affect the response to ACh and KCl, except when high doses were used, suggests that the venom presents a primordial presynaptic nature. Such neuromuscular blockade characteristics have been attributed to presynaptic-acting PLA 2 from snake [45, 46] as those of Crotalus durissus terrificus [47], Micrurus species [48, 49], and other Bothrops , Bothrops insularis [50], Bothrops pauloensis [47, 51], and Bothriopsis bilineata smargadina [52], which did not show any detectable effect on the nicotinic receptor and, in some cases, showed only a mild muscle alteration.…”
Section: Discussionmentioning
confidence: 99%
“…For diaphragm (DIA) functional analysis, the left hemidiaphragm was mounted, and muscle function assessed as previously described 19–21. For all groups studied, the preparation was suspended under a constant tension of 5 g in an organ bath (5 ml) containing aerated (95% O 2 ‐5% CO 2 ) Tyrode solution (pH 7.4, 37°C) with the following composition: 137 mM NaCl, 2.7 mM KCl, 1.8 mM CaCl 2 , 0.49 mM MgCl 2 , 0.42 mM NaH 2 PO 4 , 11.9 mM NaHCO 3 , and 11.1 mM glucose.…”
Section: Methodsmentioning
confidence: 99%